2008
DOI: 10.1093/tropej/fmn049
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-to-Severe Anaemia due to Afebrile Plasmodium falciparum Infection in Children aged 6-23 Months from the Rural District of Kongoussi, Burkina Faso

Abstract: A population-based cross-sectional study was conducted to investigate the association of haemoglobin concentration and moderate-to-severe anaemia with afebrile Plasmodium falciparum (PF) infection in 456 rural children aged 6-23 months. Capillary blood was obtained for haemoglobin concentration measurement by HemoCue and malaria detection by blood smear microscopy. Anaemia was noted in 444 (97.4%) children with 194 (42.5%) being moderate-to-severe anaemia. PF infection was noted in 240 (52.6%) children with 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Of the 13 studies that investigated associations between stunting (or lowered HAZ) and anemia, 7 found associations. 4,12,14,15,23,25,28 Although stunting was consistently shown to lower hemoglobin across the studies, the magnitude and precision of the estimates varied substantially. Wasting (or lowered WHZ) was investigated in only 6 studies and was associated with anemia in 3.…”
Section: Study Characteristics and Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Of the 13 studies that investigated associations between stunting (or lowered HAZ) and anemia, 7 found associations. 4,12,14,15,23,25,28 Although stunting was consistently shown to lower hemoglobin across the studies, the magnitude and precision of the estimates varied substantially. Wasting (or lowered WHZ) was investigated in only 6 studies and was associated with anemia in 3.…”
Section: Study Characteristics and Resultsmentioning
confidence: 98%
“…4,[12][13][14][20][21][22][23][24][25][26][27][28] Nutritional status was a less consistent correlate of anemia. Of the 13 studies that investigated associations between stunting (or lowered HAZ) and anemia, 7 found associations.…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We calculated the sample size to allow for the detection of a between-group difference of 7 g/l in Hb concentration at 80 % power and 5 % two-side type error, assuming a standard deviation of 13 g/l. These hypotheses were based on published studies (19,23) . We needed to include at least fifty-three children per group to compare endpoint Hb concentration that was the main evaluation criterion.…”
Section: Study Design and Subjectsmentioning
confidence: 99%